Is the 'happy wanderer' really happy? Transport and life satisfaction among older teenagers in rural New Zealand. (September 2018) - Ward, Aimee L.; Cameron, Claire; McGee, Rob; Freeman, Claire; Gendall, Philip J.
Highlights: Transport-related issues appear to influence life satisfaction among older adolescents. There were gender differences among transport issues, and among predictors of life satisfaction. Life satisfaction was associated with driver's licensing, cycling, and geographic location. Findings support subsidised public transport and changes to gender-neutral school uniforms.